Sustainability Analysis of Bali Cattle Farming (Bos Javanicus) in Tebo District - P. Yulianso; A. M. Fuah; R. Priyanto; Salundik (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Tebo Regency is known as one of the centers for beef cattle farming in Jambi Province. Raising Balinese cattle on people’s farms is dominated by local cattle, especially Bali cattle (Bos javanicus). The study aims to stop the business index for Bali cattle farming integrated with oil palm plantations in Tebo Regency on intensive and extensive rearing patterns. This research uses a survey method, a longing index using a Multidimensional Scaling (MDS) approach called Rap-CP (Cattle Palm), a modified approach from the rapfish program. Multidimensional scaling (MDS) RAP-CP method (palm cattle). The results of the analysis of the inventory index values for the economic, legal-institutional, technological-infrastructural, socio-cultural and ecological dimensions of intensive and widespread maintenance patterns, respectively in the categories entirely sustainable (68.72) and very sustainable (88.44), entirely sustainable (67.05) and less sustainable (40.67), entirely sustainable (55.34) and less sustainable (32.87), less sustainable (39.94) and less sustainable (37.04), quite sustainable (52.46) and entirely (74.41). The results of sustainability index analysis indicate that Tebo Regency has sustainable potential for establishing a Bali cattle farming enterprise using an extensive rearing system.